A Brief Review of RASFF Notifications on Fruit and Vegetables, 1st Semester 2022-2023 - Iuliana CONDULET; Silvius STANCIU (Communications of International Proceedings, 2023)
This paper presents a comparison between the quality of imported food products sold at European, national and Constanța County levels. The alert, information and border rejection notifications sent by the Rapid Alert System for Food and Feed (RASFF) have been used in the research, in order to assess the quality of the food products. The European consumers’ demand for safe food is the main cause of the increase in imports. In terms of influencing factors, the effects of the COVID 19 crisis and the conflict in Ukraine have been taken into account, as they greatly influenced Romania’s imports. According to the obtained results, one can see that the number of notifications recorded in the first semester of the year 2023 far exceeded the level recorded in the similar period of 2022. In the RASFF notifications analyzed, the presence of unauthorized substances in imported vegetables and fruits was most frequently reported. The research carried out has proven that there is a close link between the food imports in Romania and the RASFF notifications, as well as between the quality of the sold products and the preferences of the final consumer. This paper is part of a Ph.D. thesis, and the results could be useful to the business environment and the local authorities with responsibilities in the field of the quality of the foods sold on the market.
Keywords: quality; food; import; Romania; RASFF